Study on the Mechanism and Control of Rock Burst of Coal Pillar under Complex Conditions - Xingping Lai; Huicong Xu; Jingdao Fan; Zeyang Wang; Zhenguo Yan; Pengfei Shan; Jie Ren; Shuai Zhang; Yanbin Yang (Geofluids, 2020)
In order to explore the mechanism of coal pillar rock burst in the overlying coal body area, taking W1123 working face of Kuangou Coal Mine as the engineering background, the full mining stage of W1123 is simulated by FLAC3D. It is found that the high stress concentration area has appeared on both sides of the coal pillar when W1123 does not start mining. With the advance of the working face, the high stress concentration area forms X-shaped overlap. There is an obvious difference in the stress state between the coal pillar under the solid coal and the coal pillar under the gob in W1123. The concrete manifestation is that the vertical stress of the coal pillar below the solid coal is greater than the vertical stress of the coal pillar below the gob. The position of the obvious increase of the stress of the coal pillar in the lower part of the solid coal is ahead of the advancing position of the working face, and the position of the obvious increase of the stress of the lower coal pillar in the gob lags behind the advancing position of the working face. At the same time, in order to accurately reflect the true stress environment of coal pillars, the author conducted a physical similarity simulation experiment in the laboratory to study the local mining process of the W1123 working face, and it is found that under the condition of extremely thick and hard roof, the roof will be formed in the gob, the mechanical model of roof hinged structurer is constructed and analyzed, and the results show that the horizontal thrust of roof structure increases with the increase of rotation angle. With the development of mining activities, the self-stable state of the high stress balance in the coal pillar is easily broken by the impact energy formed by the sudden collapse of the key strata. Therefore, the rock burst of coal pillar in the overlying coal body area is the result of both static load and dynamic load. In view of the actual situation of the Kuangou Coal Mine, the treatment measures of rock burst are put forward from the point of view of the coal body and rock mass.